Mode-locked Yb-doped all-fiber laser based on in-fiber acoustooptic modulation - Villegas García, Irma Lorena (2011)
We show what we believe is the first demonstration of an ytterbium-doped strictly all-fiber active mode-locking laser. The active control of the laser is based on in-fiber amplitude modulation at 11 MHz, which is achieved by using an all-fiber acoustooptic superlattice modulator driven by standing acoustic waves. In our experiments, the laser was operated at 1091.3 nm and had two stable regimes producing either a train of modelocked single pulses or a train of pulse pairs. Best results for the modelocked train of single pulses were 740 ps of time width and 26 mW of average power, at a pump power of 480 mW.